(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This article deals with the problems the concept of reality entails – from a critical viewpoint– in the field of social studies. first, constructive grounds are presented, which examine and view the concept of reality as an objective reality. then, the risks idealism implies are identified; and the grounding of constructivism is set in regard with such an uncertainty. finally, based on a criticism of idealistic conventions not well clarified by constructivism, an outline on the idea of reality, not relying on Old or modern realism, is set forth, which surpasses the limitations of idealism, putting the notion on autonomy in a risky position. this is key to the traditional concept of reality.